2020
DOI: 10.1038/s41598-020-70803-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteins involved in the endoplasmic reticulum stress are modulated in synovitis of osteoarthritis, chronic pyrophosphate arthropathy and rheumatoid arthritis, and correlate with the histological inflammatory score

Abstract: 2D-nano-UPLC-ESI-Q-Orbitrap 2 Dimensional-nano-ultra performance liquid chromatography-electrospay ionization-Q-Orbitrap CALR Calreticulin CPPA Chronic pyrophosphate arthropathy CRP C-reactive protein DAMPS Damage-associated molecular patterns ER Endoplasmic reticulum ERAD ER-associated degradation FLS Fibroblast-like synoviocytes GRP78 Glucose-regulated protein 78 kDa LC-MS/MS Liquid chromatography-tandem mass spectrometry LFQ Label free quantification MRI Magnetic resonance imaging OA Osteoarthritis PMN Poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Since synovitis and joint inflammation alters the normal collagen synthesis-degradation coupling and contribute to loss of articular cartilage matrix and OA development (1,4,13), we sought to determine the effect of COX and sEH inhibition on the collagendegradation relationship during synovitis. As shown in Figure 5, CPII concentrations were not significantly different during inhibition of COX, sEH, or both whereas C2C concentrations were significantly lower during sEH inhibition compared to COX inhibition and the lowest dose of combined COX and sEH inhibition.…”
Section: Combined Cox and Seh Inhibition Provides Superior Protection Of The Articular Cartilage Matrix Than Inhibiting Cox Alonementioning
confidence: 99%
See 1 more Smart Citation
“…Since synovitis and joint inflammation alters the normal collagen synthesis-degradation coupling and contribute to loss of articular cartilage matrix and OA development (1,4,13), we sought to determine the effect of COX and sEH inhibition on the collagendegradation relationship during synovitis. As shown in Figure 5, CPII concentrations were not significantly different during inhibition of COX, sEH, or both whereas C2C concentrations were significantly lower during sEH inhibition compared to COX inhibition and the lowest dose of combined COX and sEH inhibition.…”
Section: Combined Cox and Seh Inhibition Provides Superior Protection Of The Articular Cartilage Matrix Than Inhibiting Cox Alonementioning
confidence: 99%
“…In equine and human OA, local and systemic release of cytokines such as tumor necrosis factor (TNF)-α and interleukin (IL)-6 are associated with pain (lameness) as well as greater loss of cartilage volume and joint space narrowing (6)(7)(8)(9). As actively secreting cells, chondrocytes are especially susceptible to endoplasmic reticulum (ER) stress, an important mechanism leading to chondrocyte apoptosis (10)(11)(12) which also correlates with synovitis in OA (13).…”
Section: Introductionmentioning
confidence: 99%
“…DNMT inhibitors can play an anti-tumor role in colon and ovarian cancer by up-regulating B2M and CALR [ 46 ]. GANAB and CANX belong to endoplasmic reticulum protein chaperones, which cooperate with CALR to regulate endoplasmic reticulum stress in osteoarthritis and asthma, respectively [ 47 , 48 ]. In triple-negative breast cancer patients, down-regulation of CALR and TAPBP tend to indicate a poor prognosis [ 49 ].Previous studies have shown that the carcinogenic mechanism of CALR is related to the exposure of malignant primordial cells to CALR, HSP70 and HSP90 on the plasma membrane [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding synovial biopsies, as used for immunohistochemistry (Figure 1), samples of synovial biopsies were retrospectively selected from our local cohort of OA patients: the synovial biopsies of OA patients (n = 16) were obtained by needle arthroscopy from affected knees. Samples were extracted and stocked as previously described by de Seny et al [8]. Patients were mostly female, with a median age of 58 years (range 29-89) and a median BMI of 30 kg/m 2 (range 18-42).…”
Section: Patient Recruitmentmentioning
confidence: 99%
“…The synovial membrane is no longer considered a bystander in OA: synovial hypertrophy is found in 1/3 of patients with OA [6] and this synovitis is associated with subsequent OA development [7]. Chronic low-grade inflammation is present in the synovial membrane; infiltration by immune cells [8] and the cross-talk between cartilage and synovial cells have a major role in OA pathogenesis [9]. In addition, we identified senescent cells in the synovium of OA mice [10] and Diekman et al demonstrated that cartilage senescence could not be the only driver of the pathology [11].…”
Section: Introductionmentioning
confidence: 99%